المسؤولية القانونية للمسير في شركة المساهمة - عبد الكبير أيمن /حساني سلمى (جامعة المسيلة, 2021)
لا أستطيع أن أقول إن تحديد مسؤولية المسيرين يعني إرساء المبادئ العامة التي تحكم هذه المسؤولية والقدرة على مراقبة المؤشرات التي يتم من خلالها وضع معايير المسؤولية ، لأنه من الصعب أحيانًا تحديد أخطاء الإدارة ، والسؤال يعود إلى المفاهيم التقليدية للخطأ في بعض الأحيان والمعاني الجديدة التي تساهم في تنظيم المسؤولية يجب أن تكون هذه المسؤولية ذات أهمية قصوى ، أولاً على المستويين العقائدي والتشريعي وثانيًا على المستوى القضائي. غالبًا ما يقتصر القضاء دراسته على فحص المسؤولية في السياق الجنائي ، بحيث لا توجد أحكام قضائية يمكن استخدامها لتحديد مفهوم الخطأ في السلوك وتحديد موقف القضاء من طبيعة المسؤولية. I couldn't tell thDetermining the responsibility of managers means establishing the general principles governing this responsibility and the ability to monitor the indicators through which the criteria for responsibility are established, because it is sometimes difficult to identify management errors, and the question is due to the sometimes traditional concepts of error and new meanings that contribute to regulating the responsibility of This responsibility should be of paramount importance, first at the doctrinal and legislative levels and then second at the judicial level. The judiciary often confines its study to examining liability in the criminal context, so that there are no judicial decisions that can be used to define the concept of error in conduct and to determine the attitude of the judiciary to the nature of the responsibility of .
Keywords: المسؤولية القانونية - شركة المساهمة